Kinerja DP3AP2KB Kota Denpasar dalam Menangani Kekerasan Dalam Rumah Tangga Tahun 2018 - Dorothy, Yolanda Patricia; Yudartha, I Putu Dharmanu; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2019)
ABSTRACT The aim of this research is to understand the performance of Women Empowerment and Child Protection, Population Control, and Family Planning Office of Denpasar City in handling domestic violence in 2018. The indicators used to examine performance of Women Empowerment and Child Protection, Population Control, and Family Planning Office of Denpasar City is Dwiyanto’s measurement of performance which are Productivity, Service Quality, Responsivity, Responsibility, and Accountability. The research method used are descriptive qualitative with data collection from observation, interview, and documentation study. The outcome of this research showed that performance of Women Empowerment and Child Protection, Population Control, and Family Planning Office of Denpasar City in handling domestic violence haven’t been run optimally in 2018. There are still some obstacles that causes domestic violence cases haven’t been handled optimally which are unspecified time period of case-solving, unmaximized access of information because of uncomprehensive socialization, and no responsibility to the society. Keywords: Performance, Women Empowerment and Child Protection, Population Control and Family Planning Office, Domestic Violence